Spatial regulation of ARAF controls the MST2-Hippo pathway - Rauch, Jens (Small GTPases, 2017)
The RAF-MAPK signaling pathway regulates several very diverse cellular processes such as proliferation, differentiation, apoptosis, and transformation. While the canonical function of RAF kinases within the MAPK pathway is the activation of MEK, our group could demonstrate an important crosstalk between RAF signaling and the pro-apoptotic mammalian sterile 20-like kinase (MST2) tumor suppressor pathway in several cancer entities, including head and neck, colon, and breast. Here, the RAF kinases CRAF and ARAF sequester and inhibit the pro-apoptotic kinase MST2 independently of their own kinase activity. In our recent study, we showed that the ARAF-MST2 complex is regulated by subcellular compartmentalization during epithelial differentiation. Proliferating cells of the basal cell layer in squamous epithelia and tumor cells express ARAF at the mitochondria thus allowing for efficient sequestration of MST2. In contrast, non-malignant squamous epithelia have ARAF localized at the plasma membrane, where the control of MST2-mediated apoptosis is compromised. This re-distribution is regulated by the scaffold protein kinase suppressor of Ras 2 (KSR2). Here, we summarize how spatial and temporal regulation of RAF signaling complexes affect cellular signaling and functions.